Pengaruh Karakteristik Merek, Karakteristik Perusahaan dan Karakteristik Merek Pelanggan terhadap Loyalitas Pelanggan Outlet Planet Surf di Yogyakarta - Argiansyah, Aris; Handayani, Siti Dyah (Jurnal Manajemen Bisnis, 2015)
This research aims to investigate the effect of brand characteristic, company characteristic and customer’s brand characteristic toward customer’s loyalty in Outlet Planet Surf Yogyakarta.This research is quantitative in nature by using survey method with questionnaire. The population of the research is the customer in Outlet Planet Surf Yogyakarta, by using the criteria of customer who made a purchase transaction at least once in the last three months. The samples are 100 respondents by using purposive sampling technique. The method of analysis being used is the quantitative analysis which include: validity test and reliability test, double linear regression, and the hypothesis is tested by using Individual Parameter Significance Test (statistical test t), simultaneous significance test (statistical test f) and determination coefficient analysis (R2). The result of the research shows that simultaneously the three free variables which are brand characteristic (X1), company characteristic (X2), and customer’s brand characteristic (X3) positively and significantly affect the customer’s loyalty (Y). Partial test also shows that all of the respective variables positively and significantly affect the customer’s loyalty.